2023
DOI: 10.3390/cells12101352
|View full text |Cite
|
Sign up to set email alerts
|

Live Cell Imaging of ATP Levels Reveals Metabolic Compartmentalization within Motoneurons and Early Metabolic Changes in FUS ALS Motoneurons

Abstract: Motoneurons are one of the most energy-demanding cell types and a primary target in Amyotrophic lateral sclerosis (ALS), a debilitating and lethal neurodegenerative disorder without currently available effective treatments. Disruption of mitochondrial ultrastructure, transport, and metabolism is a commonly reported phenotype in ALS models and can critically affect survival and the proper function of motor neurons. However, how changes in metabolic rates contribute to ALS progression is not fully understood yet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 101 publications
0
1
0
Order By: Relevance
“…In addition, it has been recently shown that increased demand for NAD + relative to ATP induces aerobic glycolysis (Luengo et al, 2021). We recently showed that a boosted metabolic turnover of the glycolytic pathway improved the viability of FUS-ALS MN, whereas blocking glycolysis reduced their viability (Zimyanin et al, 2023). These data altogether suggest that the beneficial treatment effect of GA and DL in FUS-and SOD1-ALS MNs might be because of a metabolic rescue by restoring the NAD(P)H reservoir.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, it has been recently shown that increased demand for NAD + relative to ATP induces aerobic glycolysis (Luengo et al, 2021). We recently showed that a boosted metabolic turnover of the glycolytic pathway improved the viability of FUS-ALS MN, whereas blocking glycolysis reduced their viability (Zimyanin et al, 2023). These data altogether suggest that the beneficial treatment effect of GA and DL in FUS-and SOD1-ALS MNs might be because of a metabolic rescue by restoring the NAD(P)H reservoir.…”
Section: Discussionmentioning
confidence: 84%
“…DJ-1 is integral for maintaining mitochondrial potential, Ca 2+ homeostasis and ATP production. Of note, loss of DJ-1 did not affect mitochondrial respiration but increased ROS production and mitochondrial permeability transition pore opening (Giaime et al, 2012), phenotypes which we recently identified also in FUS-ALS MNs (Zimyanin et al, 2023). GA can support the mitochondrial membrane potential and neuronal survival (Toyoda et al, 2014), improve mitochondrial energy production, thereby increasing the levels of NAD(P)H (Bour et al, 2021 Preprint) and can also reduce oxidative stress via a glutathione-mediated pathway (Diez et al, 2021).…”
Section: Introductionmentioning
confidence: 75%
“…FUS-ALS pathophysiology was associated with significant mitochondrial dysfunction. Specifically, axonal mitochondrial transport was shown to be impaired, as well as mitochondrial depolarization, which was obvious when observed together with the impacted metabolic state of FUS-mutated neurons [33,34]. We first investigated whether this mitochondrial phenotype is also seen in HeLa cells engineered to carry either wild-type FUS-eGFP or P525L FUS-eGFP.…”
Section: Mitochondrial Depolarization In Fus-mutated Cellsmentioning
confidence: 99%